PENGARUH DITERAPKANNYA E-FILING DALAM PERPAJAKAN DI ERA DIGITALISASI 4.0 TERHADAP KEPATUHAN MASYARAKAT DALAM MEMBAYAR PAJAK DI INDONESIA - Frendika, Eka (Universitas Pembangunan Panca Budi, 2023)
Tax is a contribution from the people to the state treasury based on law that can be enforced without receiving direct reciprocal services that can be shown and which are used to pay for general expenses